Employees' Upward Hostility: A Specific Phenomenon of Ethical Leadership - Siebens, Herman (Ethical perspectives, 2019)
This article focuses on the specific issue of a formal leader/supervisor being confronted with upwards hostility by some of his/her subordinates (possibly informal leaders or middle managers). Why would a supervisor attempting an ethical leadership style be (more) vulnerable to this kind of hostile behaviour? We thus address employee-leader conflict, albeit within a group and institutional context. By means of a multidisciplinary literature review (including psychology, social psychology, sociology, criminology, ethics, philosophy) we will explain how and why a supervisor can be confronted with "upwards hostility of employees". The notion of "dark personality" will further guide us in the intrinsic characteristics of anti-social and destructive behaviour which we will analyse as self-centred and self-regarding. Furthermore, we will endeavour to clarify why an ethical leadership style - defined as facilitating - should make a supervisor more vulnerable to upwards hostility. We conclude by explaining some specific phenomena, such as "the bystander", "ethical disengagement" and the "noble nature". The final section briefly summarises some ideas on how to tackle upwards hostility by subordinates within an ethical framework. The article concludes with a short scientific discussion and a preview of further research into the phenomenon of upwards hostility. Since the literature review has yielded little or no clear reference to this phenomenon, we believe that this is a truly new theme. To the extent that the article sets out to reframe the phenomena of hostility and abusive leadership, and illustrates the destructive and toxic character of upwards hostility against a formal supervisor, organizational policymakers should be aware of it. Ultimately, the article is an attempt to break the taboo of the upwards hostility of employees (sometimes middle-managers) against their formal leader, and to question the false generalization (popular belief) that this is always the consequence and outcome of an abusive style of leadership by the formal leader himself ("blaming the victim").